Epigenetics in Sepsis: Understanding Its Role in Endothelial Dysfunction, Immunosuppression, and Potential Therapeutics - Cross, Deborah; Drury, Ruth; Hill, Jennifer; Pollard, Andrew J. (Frontiers in Immunology, 2019)
Sepsis has a complex pathophysiology in which both excessive and refractory inflammatory responses are hallmark features. Pro-inflammatory cytokine responses during the early stages are responsible for significant endothelial dysfunction, loss of endothelial integrity and organ failure. In addition, it is now well established that a substantial number of sepsis survivors experience ongoing immunological derangement and immunosuppression following a septic episode. The underpinning mechanisms of these phenomena are incompletely understood yet they contribute to a significant proportion of sepsis-associated mortality. Epigenetic mechanisms including DNA methylation, histone modifications and non-coding RNAs, have an increasingly clear role in modulating inflammatory and other immunological processes. Recent evidence suggests epigenetic mechanisms are extensively perturbed as sepsis progresses, and particularly play a role in endothelial dysfunction and immunosuppression. Whilst therapeutic modulation of the epigenome is still in its infancy, there is substantial evidence from animal models that this approach could reap benefits. In this review, we summarize research elucidating the role of these mechanisms in several aspects of sepsis pathophysiology including tissue injury and immunosuppression. We also evaluate pre-clinical evidence for the use of “epi-therapies” in the treatment of poly-microbial sepsis.